2007
DOI: 10.1142/s0192415x07004898
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Tai Chi and Resistance Training on Bone Metabolism in the Elderly: A Feasibility Study

Abstract: This feasibility study compared the effects of Tai Chi (TC) and resistance training (RT) on bone metabolism in the elderly. Twenty eight sedentary, elder adults, were randomized into either TC (n = 14, 78.8 +/-1.3 years) or RT (n = 14, 79.4 +/-2.2 years) to participate in 40 min of exercise per session, 3 sessions/week for 24 weeks. The outcome measures assessed were the concentrations of serum bone-specific alkaline phosphatase (BAP), pyridinoline (PYD), parathyroid hormone (PTH) and calcium, and urinary calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 32 publications
2
31
0
1
Order By: Relevance
“…The review included three studies which examined Tai Chi and its effect in older adults specifically [88][89][90], but all were found only to be of moderate methodological quality. Amongst healthy but sedentary older adults Tai Chi was found to stimulate bone metabolism significantly more than resistance training [90].…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
See 1 more Smart Citation
“…The review included three studies which examined Tai Chi and its effect in older adults specifically [88][89][90], but all were found only to be of moderate methodological quality. Amongst healthy but sedentary older adults Tai Chi was found to stimulate bone metabolism significantly more than resistance training [90].…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
“…Although, in frail institutionalised older adults it was found to increase bone density and reduce fracture rate [88]. Nonetheless, the studies included in the Lee et al [87] review measured bone mineral density in different ways, such as BMD [88,89] or bone metabolism [90] and therefore it is difficult to make direct comparisons between studies, with no further studies identified.…”
Section: Bone Density and Osteoporosismentioning
confidence: 99%
“…A substantial body of research suggests TC training may reduce falls and associated risk factors [5-8]. A handful of studies have evaluated the direct effects of TC on BMD [9-13]. However, few studies are randomized trials, most have significant methodological limitations, and we are not aware of any trials that have evaluated the impact of TC on both BMD and postural control in osteopenic women [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…In another study, we found that 6 weeks of TC exercise induced an increase in serum bone formation biomarker (bone-specific alkaline phosphatase, BAP) in healthy elderly participants [27]. Further, postmenopausal women with lower lean muscle mass or strength are at a higher risk for osteoporosis [3236], while GTP [3741] and TC [42, 43] may improve muscle strength.…”
Section: Introductionmentioning
confidence: 99%